Manajemen Risiko Investasi Dana Haji Sebagai Upaya Pengembangan Dana Tepat Guna - Novi Tri Oktavia; Anita Febriani; Binti Nur Asiyah; Rokhmat Subagiyo; Dwi Astuti Wahyu Nurhayati (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2023)
This research has the background that the investment risk of Bank Syariah Indonesia is a risk that is absolutely faced by Islamic banking where investment risk occurs because the bank also bears the losses of customers who are financed in profit-sharing based financing. This research aims to determine whether there are differences in the risk management of Hajj investment funds at Indonesian Sharia Banks and other Islamic financial institutions. This type of research is qualitative research. The method used is a case study. The population used is Bank Syariah Indonesia, the Tulungagung Sudirman Sub-Branch Office, which has been operating since 1 February 2021 as Bank Syariah Indonesia (BSI) because there are merger of three Islamic State-Owned Enterprises (BUMN) Islamic banks. Based on the results of research on the application of hajj fund investment risk management at BSI KCP Tulungagung Sudirman is by synchronizing or adjusting tools, methodologies, policies and standard procedures covering governance and risk management aspects of hajj fund investment used by central BSI and BSI KCP Tulungagung Sudirman, as well as Development of a risk management information system for investment in Hajj funds by taking into account the needs and availability of supporting infrastructure.